Procedimientos administrativos-financieros y niveles de eficiencia del área financiera y negocios de la Cooperativa de Ahorro y Crédito " 9 de Octubre LTDA. ", Del cantón Salcedo correspondiente al período 2012. Propuesta manejo de un cuadro de mando integral ( BALANCED SCORECARD). - Espín Balseca, Lorena del Rocío (2015)
The research was conducted in order to assess the level of compliance with the strategic planning of the “Cooperativa de Ahorro y Crédito 9 de Octubre Ltda.”, , through the balanced scorecard management to the financial and business area which was considered strategic issues , objectives, indicators , targets and initiatives that were established in strategic planning and this will help to ensure proper management for making decisions, being very important for institutional benefit , since you can verify compliance with the objectives of the entity, the relationship with their environment, and their operations . The research was applied was as a bibliographic type to base the variables in the same field as was done in the place where events developed and allow for solving the problems in operational and administrative management of the institution. The information was obtained through the use of instruments such as inquest, the same as those applied to financial and business area of the company. The Balanced Scorecard was performed to obtain a diagnosis and find the weaknesses and based on them improve on administrative and financial management focusing on achievement of objectives through the implementation of indicators in each of the financial and customer perspectives so to assess the fulfillment of the goals that destine to conclude the degree of efficiency in each of them with proper optimization of existing resources.